The mechanoreceptor DEG‐1 regulates cold tolerance in Caenorhabditis elegans. (3rd February 2020) - Takagaki, Natsune; Ohta, Akane; Ohnishi, Kohei; Kawanabe, Akira; Minakuchi, Yohei; Toyoda, Atsushi; Fujiwara, Yuichiro; Kuhara, Atsushi
Abstract: Caenorhabditis elegans mechanoreceptors located in ASG sensory neurons have been found to sense ambient temperature, which is a key trait for animal survival. Here, we show that experimental loss of xanthine dehydrogenase (XDH‐1) function in AIN and AVJ interneurons results in reduced cold tolerance and atypical neuronal response to changes in temperature. These interneurons connect with upstream neurons such as the mechanoreceptor‐expressing ASG. Ca 2+ imaging revealed that ASG neurons respond to warm temperature via the mechanoreceptor DEG‐1, a degenerin/epithelial Na + channel (DEG/ENaC), which in turn affects downstream AIN and AVJ circuits. Ectopic expression of DEG‐1 in the ASE gustatory neuron results in the acquisition of warm sensitivity, while electrophysiological analysis revealed that DEG‐1 and human MDEG1 were involved in warm sensation. Taken together, these results suggest that cold tolerance is regulated by mechanoreceptor‐mediated circuit calculation. Synopsis: A DEG/ENaC‐type mechanoreceptor‐mediated neural circuit regulates cold tolerance in Caenorhabditis elegans . The lack of xanthine dehydrogenase (XDH‐1) in AIN and AVJ interneurons results in defective cold tolerance. DEG‐1, a DEG/ENaC‐type mechanoreceptor regulates warm sensitivity of ASG sensory neurons, which affect downstream AIN and AVJ circuits. Ectopic expression of DEG‐1 in C. elegans gustatory neuron or in Xenopus oocytes is sufficient to confer warm sensitivity. Abstract : A DEG/ENaC‐type mechanoreceptor‐mediated neural circuit regulates cold tolerance in Caenorhabditis elegans .